Does Gender Difference Play a Significant Role in Verbal and Visuospatial Working Memory Performance? - Chan, Zhi Shan; Mohamad Azhari, Abu Bakar (UNIMAS Publisher, 2021)
The present study investigates gender differences in working memory performance, both verbal and visuospatial working memory performance. Quasi-experimental research was conducted individually on 32 undergraduates at a public university in Malaysia, using a reading span task and rotation span task. The performance was based on the total number of correct recalled and the total time taken. Results showed a significant gender difference in the verbal and visuospatial working memory performance. The observation was based on the total time taken, in which males performed more rapidly than females in both tasks. In terms of accuracy, female participants recalled better than their male counterparts in the verbal task, which is consistent with numerous past studies. However, no gender difference was identified in the visuospatial task performance, based on the total number of correct recalled. The study also found that male participants did not show an advantage in visuospatial abilities, contradicting findings by past studies.